Overriding follicle selection in controlled ovarian stimulation protocols: Quality vs quantity - Zelinski-Wooten Mary B; Stouffer Richard L (BMC, 2004)
Abstract Selection of the species-specific number of follicles that will develop and ovulate during the ovarian cycle can be overridden by increasing the levels of pituitary gonadotropin hormones, FSH and LH. During controlled ovarian stimulation (COS) in nonhuman primates for assisted reproductive technology (ART) protocols, the method of choice (but not the only method) has been the administration of exogenous gonadotropins, either of nonprimate or primate origin. Due to species-specificity of the primate LH (but not FSH) receptor, COS with nonprimate (e.g., PMSG) hormones can be attributed to their FSH activity. Elevated levels of FSH alone will produce large antral follicles containing oocytes capable of fertilization in vitro (IVF). However, there is evidence that LH, probably in lesser amounts, increases the rate of follicular development, reduces heterogeneity of the antral follicle pool, and improves the viability and rate of pre-implantation development of IVF-produced embryos. Since an endogenous LH surge typically does not occur during COS cycles (especially when a GnRH antagonist is added), a large dose of an LH-like hormone (i.e., hCG) may be given to reinitiate meiosis and produce fertilizable oocytes. Alternate approaches using exogenous LH (or FSH), or GnRH agonist to induce an endogenous LH surge, have received lesser attention. Current protocols will routinely yield dozens of large follicles with fertilizable eggs. However, limitations include non/poor-responding animals, heterogeneity of follicles (and presumably oocytes) and subsequent short luteal phases (limiting embryo transfer in COS cycles). However, the most serious limitation to further improvements and expanded use of COS protocols for ART is the lack of availability of nonhuman primate gonadotropins. Human, and even more so, nonprimate gonadotropins are antigenic in monkeys, which limits the number of COS cycles to as few as 1 (PMSG) or 3 (recombinant hCG) protocols in macaques. Production and access to sufficient supplies of nonhuman primate FSH, LH and CG would overcome this major hurdle.